2018
DOI: 10.2478/frp-2018-0007
|View full text |Cite
|
Sign up to set email alerts
|

The influence of atmospheric light scattering on reflectance measurements during photogrammetric survey flights at low altitudes over forest areas

Abstract: In this article, we describe methods for the correction of multispectral aerial images by accounting for atmospheric interference. We also summarize the first correction results for images acquired at flight altitudes and evaluate the suitability of selected methods for the atmospheric correction of these images. Furthermore, processes and phenomena occurring in the atmosphere that potentially affect image quality and interfere with the electromagnetic radiation registered by the imaging sensors are discussed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Also, the highest amount of water vapour in the atmosphere is at the Earth's surface, and decreases with altitude. For example, at the height of 1500 m, the average concentration of water vapour is 50% lower than at the Earth's surface, and at the height of 5000 m, the content is already ten times lower [2,3]. Under such conditions, radiation passing through the atmosphere is absorbed and dispersed by suspensions of small water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the highest amount of water vapour in the atmosphere is at the Earth's surface, and decreases with altitude. For example, at the height of 1500 m, the average concentration of water vapour is 50% lower than at the Earth's surface, and at the height of 5000 m, the content is already ten times lower [2,3]. Under such conditions, radiation passing through the atmosphere is absorbed and dispersed by suspensions of small water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In order to avoid similar problems in subsequent missions, it was decided to perform additional tests of devices in the cryochamber and to undertake a series of intensive tests of the efficiency of several types of batteries for extreme temperatures down to -60°C. The goal of such tests would be determining the electrical parameters of battery or battery packs, with and without radiators, during their operation in changing environmental conditions [15].…”
Section: Initial Assumptions and Implementation Of The Missionmentioning
confidence: 99%
“…Performance testing of the system of dehazing suggested had been performed by only using subjective metrics like the SSIM, PSNR, RMS, normalized crosscorrelation, Universal Image Quality Index, the root mean square error (RMSE). Investigations showed that utilizing the dehazing algorithm, could minimize the adverse effects of haze and enhance the quality of aerial imagery dependent on the PSNR scale [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%